2021
DOI: 10.1097/aln.0000000000003986
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Change of Cortical Hemodynamic Signals Associated with Ongoing Nociception in Awake and Anesthetized Individuals: An Exploratory Functional Near Infrared Spectroscopy Study

Abstract: Background Patients undergoing surgical procedures are vulnerable to repetitive evoked or ongoing nociceptive barrage. Using functional near infrared spectroscopy, the authors aimed to evaluate the cortical hemodynamic signal power changes during ongoing nociception in healthy awake volunteers and in surgical patients under general anesthesia. The authors hypothesized that ongoing nociception to heat or surgical trauma would induce reductions in the power of cortical low-frequency hemodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…They found that injection of local anesthetics (a painful stimulus itself) prior to skin incision induced an instantaneous increase in both oxyhemoglobin and total hemoglobin content the prefrontal cortex are comparable between the awake and anesthetized states. 5 Together, these data should stimulate innovative efforts to improve perioperative nociception. Indeed, as frustrating as it is, our current clinical practice to monitor pain during the intraoperative period is mostly based on indirect proxies such as blood pressure, heart rate, and movements-an approximate and rudimentary practice.…”
Section: Near-infrared Spectroscopy: More Than Just Monitoring Brain ...mentioning
confidence: 98%
“…They found that injection of local anesthetics (a painful stimulus itself) prior to skin incision induced an instantaneous increase in both oxyhemoglobin and total hemoglobin content the prefrontal cortex are comparable between the awake and anesthetized states. 5 Together, these data should stimulate innovative efforts to improve perioperative nociception. Indeed, as frustrating as it is, our current clinical practice to monitor pain during the intraoperative period is mostly based on indirect proxies such as blood pressure, heart rate, and movements-an approximate and rudimentary practice.…”
Section: Near-infrared Spectroscopy: More Than Just Monitoring Brain ...mentioning
confidence: 98%
“… 40 In humans, ongoing nociceptive processing has been shown to occur in adolescent patients under balanced general anesthesia. 41 …”
Section: State Ii: Perioperative Approachesmentioning
confidence: 99%
“… 55 , 56 Our group has been evaluating a technology (functional near-infrared spectroscopy, fNIRS) for measures of nociception and pain in adult and pediatric populations during both awake and unconscious/anesthetized states. 41 , 57–59 Low susceptibility to motion artifacts, flexibility in setup, and low overhead cost make fNIRS a useful neuro-investigative tool for a wide range of research and clinical applications involving pediatric patients. It is a popular technique to investigate typical and atypical development in infants, 60–62 young children, 63 , 64 and adolescents.…”
Section: State Ii: Perioperative Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…over time-there is no gold standard for the quantitative monitoring of nociception intraoperatively, and anesthesiologists titrate analgesics based on autonomic responses via the nociceptive autonomic responses as surrogates; available nociception monitors generate an analgesic index derived from physiologic (mainly autonomic) signals rather than quantifying nociception directly from the central nervous system [65,66]. We have reported on each of these separately [18,67] but not in terms of overall pain load that may contribute to enhanced central sensitization; further research is necessary to define thresholds for intervention; (2) Definition of sensitivity and specificity of fNIRS measures-although the activation's are context specific, other activations while under anesthesia may need to be evaluated in both awake and anesthetized patients as we have recently reported for painful stimuli [67]; (3) Measures across anesthetic type (e.g., inhalational versus nerve block versus combination) is also necessary; (4) The importance of maintaining optimal analgesia through surgery to inhibit subsequent acute and chronic pain/analgesic use-further work is required to quantitate the relationship of perioperative pain to sensitization and the development of chronic pain; as such, determination of presurgical factors (brain state and physiological/autonomic activity) influence the measurement of pain during surgery; and (5) Technical development-if shown to be useful, the technology will need to be developed into a format that can be used at the bedside/in the operating room.…”
Section: Plos Medicinementioning
confidence: 99%